Occurrence and antibiogram of generic extended spectrum Cephalosporin-resistant and extended-spectrum Β-Lactamase-producing Enterobacteria in horses - Madubuike Umunna Anyanwu; Ifeoma Chinyere Ugwu; Collins Uchenna Onah (Macedonian Veterinary Review, 2018)
This study was conducted to isolate generic extended-spectrum cephalosporin (ESC)-resistant and extended-spectrum β-lactamase (ESBL)-producing enterobacteria from horses in Nigeria, and to determine the antibacterial resistance profile. Rectal swabs were collected from 155, systematic randomly selected, apparently-healthy horses. Isolation of ESC-resistant enterobacteria was done using Mac Conkey agar with ceftazidime. ESBL production was assessed by combination disc method. Resistance of the isolates was determined using disc diffusion method. Out of 155 samples, 5.2% gave positive growth. From these, 11 ESC-resistant enterobacteria comprising of 36.4% E. coli, 36.4% Salmonella spp. and 27.2% Proteus spp., were obtained. From 11 isolates, 45.5% consisting of all the 4 E. coli and 1 Proteus isolates, were ESBL-producers, these were recovered from 4 (2.6%) out of the 155 horses sampled. Resistance of the E. coli isolates was 25% to aztreonam (AZT), 75% to amoxicillin-clavulanic acid (AMC), gentamicin (GEN), perfloxacin (PEF), and sulphamethoxazoletrimethoprim (SXT-TRI), 50% to ofloxacin (OFL) and 100% to ampicillin (AMP), ceftazidime (CTZ), cefotaxime (CTX), chloramphenicol (CHL), streptomycin (STR), tetracycline (TET), sparfloxacin (SPA), ciprofloxacin (CIP), norfloxacin (NOR) and enrofloxacin (ENR). Resistance of the Salmonella isolates was 50% to PEF and 100% to CTZ, CTX, AMP, AZT, AMC, CHL, GEN, STR, TET, SPA, CIP, OFL, NOR and ENR. Resistance of the Proteus isolates was 25% to AMC, CHL, STR, TET, SPA and NOR, and 100% to CTZ, CTX, AZT and AMP. Resistance of the isolates to more than 3 classes of antibacterial agents tested was 75% for Proteus and 100% for E. coli and Salmonella, respectively. This study showed that horses in Nigeria are potential reservoirs and disseminators of ESC-resistant and ESBL-producing Enterobacteriaceae.